Listeriolysin O Pore-Forming Activity Is Required for ERK1/2 Phosphorylation During Listeria monocytogenes Infection - Cheng, Changyong; Sun, Jing; Yu, Huifei; Ma, Tiantian; Guan, Chiyu; Zeng, Huan; Zhang, Xian; Chen, Zhongwei; Song, Houhui (Frontiers in Immunology, 2020)
Listeriolysin O (LLO) is a cholesterol-dependent cytolysin that mediates the escape of L. monocytogenes from phagosomes and enables the bacteria to grow within the host. LLO is a versatile tool allowing Listeria to trigger several cellular responses. In this study, rapid phosphorylation of ERK1/2 on Caco-2 cells caused by Listeria infection was demonstrated to be highly dependent on LLO activity. The effect could be strongly induced by adding purified recombinant LLO alone and could be inhibited by exogenous cholesterol. Lack of the PEST sequence, known to tightly control cytotoxicity of LLO, did not affect ERK1/2 activation. However, the recombinant non-cytolytic LLOT515AL516A, with mutations in the cholesterol-binding motif, was unable to trigger this response. Recombinant LLON478AV479A, which lacks most of the cytolytic activity, also failed to activate ERK1/2 phosphorylation, and this effect could be rescued when the protein concentration reached a cytolytic level. Infection with an LLO-deficient mutant (△hly) or the mutant complementing LLOT515AL516A abrogated the capacity of the bacteria to activate ERK1/2. However, infection with the △hly mutant complementing LLON478AV479A, which retained partial pore-forming ability and could grow intracellularly, was capable of triggering ERK1/2 phosphorylation. Collectively, these data suggest that ERK1/2 activation by L. monocytogenes depends on the permeabilization activity of LLO and more importantly correlates with the cholesterol-binding motif of LLO.